2020
DOI: 10.3389/fcvm.2020.587100
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Molecular Imaging: Near-Infrared Fluorescence as a New Frontier

Abstract: Despite exciting advances in structural intravascular imaging [intravascular ultrasound (IVUS) and optical coherence tomography (OCT)] that have enabled partial assessment of atheroma burden and high-risk features associated with acute coronary syndromes, structural-based imaging modalities alone do not comprehensively phenotype the complex pathobiology of atherosclerosis. Near-infrared fluorescence (NIRF) is an emerging molecular intravascular imaging modality that allows for in vivo visualization of pathobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…NIRF imaging is an emerging cellular and molecular imaging technique that uses laser induced NIR signal to stimulate NIRF emission of vessel wall and plaques that have injected with fluorescence-imaging agents [174]. It has been demonstrated that the activity of plaque inflammation can be detected by injecting an imaging contrast agent to the sites of the inflamed tissues [175].…”
Section: Ivus-based Multimodality Intravascular Imagingmentioning
confidence: 99%
“…NIRF imaging is an emerging cellular and molecular imaging technique that uses laser induced NIR signal to stimulate NIRF emission of vessel wall and plaques that have injected with fluorescence-imaging agents [174]. It has been demonstrated that the activity of plaque inflammation can be detected by injecting an imaging contrast agent to the sites of the inflamed tissues [175].…”
Section: Ivus-based Multimodality Intravascular Imagingmentioning
confidence: 99%
“…Thus, more than one imaging modality has been integrated into the IVUS images. For example, IVUS/intravascular optical coherence tomography (IV-OCT) [184][185][186][187][188][189] and IVUS/near-infrared spectroscopy (NIRS) [190][191][192][193][194] are currently available for practical use, and IVUS images with near-infrared fluorescence (NIRF) [195][196][197][198][199], fluorescence lifetime imaging (FLIm) [200][201][202][203][204], and intravascular photoacoustic (IVPA) [123,[205][206][207][208] have been investigated at the laboratory level. These combinations can complement the drawbacks of each imaging modality while providing more clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular ultrasound (IVUS) guidance of percutaneous coronary intervention (PCI) significantly reduces major cardiac adverse events. [ 81 ] The acquisition time of imaging of ultrasound is much faster than those of MRI, Positron Emission Computed Tomography (PET), and X‐ray. The wireless magnetic motion control and planning of soft untethered grippers demonstrated the ability of real‐time ultrasound imaging feedback, where visual feedback cannot be provided via cameras.…”
Section: The Core Capabilities and Technical Components Of Microrobots For Active Drug Deliverymentioning
confidence: 99%